LiteST: a lightweight secure time synchronization protocol for wireless sensor networks - YIN Xiang-lan; QI Wang-dong (Tongxin xuebao)
A simple approach was put forward to check the integrity of broadcast messages. Integrating with one- way-hash chain to authenticate the sender of broadcast messages and a new redundant mechanism to deal with insider at- tacks, a lightweight secure time （LiteST） synchronization protocol was proposed. Analysis and simulations show LiteST can defeat external attacks and is resilient to compromised nodes and it achieves comparable security performance against TinySeRSync, the best secure time synchronization protocol up to date. Experiments with a network of 32 Mica2 motes show that LiteST achieves much the same time precision as FTSP, a time synchronization protocol without security fea- tures. The processing cost of LiteST is about one-fifth of TinySeRSync and the communication cost 1/（2m+2） of the latter, where m is the average neighbor count of nodes in the network. In addition, the storage requirement of LiteST is much lower than TinySeRSync in practical scenarios.